If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5y + 4y + 2x = 0 Reorder the terms: 3x + 2x + -5y + 4y = 0 Combine like terms: 3x + 2x = 5x 5x + -5y + 4y = 0 Combine like terms: -5y + 4y = -1y 5x + -1y = 0 Solving 5x + -1y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 5x + -1y + y = 0 + y Combine like terms: -1y + y = 0 5x + 0 = 0 + y 5x = 0 + y Remove the zero: 5x = y Divide each side by '5'. x = 0.2y Simplifying x = 0.2y
| 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t | | 4*(x+6)= | | X(-2)+18=50(-3x)+25 | | 2*(x+3)= | | 2*(3a)= | | -24+x=36 | | (-2x)+5+3x+-4x+(-1)+(-x)= | | 2x+(-2)=17 | | 6*2s=39 | | ×/3-4=×/5-6 | | 2(-1)+y=17 | | Y+12=c | | 3/7=n/21 | | 4.5+x=-2.3 | | 10x-15=6x+14 | | 3(7+2x)=7(x-1) | | ln(5-x)=2.3 | | 7m-2t=72 | | (5+23x-3)-5=13x+20(-3) | | 15+-3x= | | 231m*j=123851 | | 3/8=n/24 |